Sociological perspectives on the new genetics - Conrad, Peter; Gabe, Jonathan (Oxford : Blackwell, 1999)
Introduction. Structure and production of genetic knowledge. The social meanings of genetics. The social impact and implications of genetics.
Keywords: Social aspects; Medical genetics; Medical genetics -- Social aspects